Sejarah Budaya "MADDOJA BINE" dalam Masyarakat Soppeng Sebagai Studi Etnografi - Dian Hajrawati; Mohammad Syafiq; Set Ahmad; Haniah Haniah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Maddoja Bine is an agrarian tradition of the Bugis people in Soppeng Regency, performed before sowing rice seeds in the nursery. This ritual contains social, religious, and cultural values ​​deeply rooted in the belief system and social structure of the local community. This study aims to examine the history, ritual procession, socio-religious dimensions, and the dynamics of change and preservation of the Maddoja Bine tradition through an ethnographic approach. The research method used is a literature study by reviewing various national and international journal sources published in the last ten years, supplemented by a qualitative analysis of the results of previous research. The results of the study indicate that Maddoja Bine functions not only as an agricultural ritual, but also as a medium for collective prayer, a means of transmitting moral values, and strengthening social solidarity in the Bugis community. Along with social change, agricultural modernization, and religious influences, this ritual has undergone transformations in form and practice, but still maintains its core values ​​as a local cultural identity. Thus, Maddoja Bine is a tradition that is dynamic and adaptive to changing times, yet remains relevant as an intangible cultural heritage of the Bugis community.